Sobre a síntese de pirróis 3,4-dissubstituídos e seus correspondentes derivados porfirínicos - Assis, Francisco Fávaro de (2014)
In this work we have developed the synthesis of 3,4-disubstituted pyrroles, aiming at the preparation of strategically designed (continue...)